Ingestion and Depuration of Microplastics by a Planktivorous Coral Reef Fish, Pomacentrus amboinensis - Santana, Marina F. M.; Dawson, Amanda L.; Motti, Cherie A.; van Herwerden, Lynne; Lefevre, Carine; Kroon, Frederieke J. (Frontiers in Environmental Science, 2021)
Microplastics are ubiquitous contaminants in marine environments and organisms. Concerns about potential impacts on marine organisms are usually associated with uptake of microplastics, especially via ingestion. This study used environmentally relevant exposure conditions to investigate microplastic ingestion and depuration kinetics of the planktivorous damselfish, Pomacentrus amboinensis. Irregular shaped blue polypropylene (PP) particles (longest length 125 to 250 µm), and regular shaped blue polyester (PET) fibers (length 600 to 700 µm) were selected based on physical and chemical characteristics of microplastics commonly reported in the marine environment, including in coral reef ecosystems. Individual adult damselfish were exposed to a single dose of PP particles and PET fibers at concentrations reported for waters of the Great Barrier Reef (i.e. environmentally relevant concentrations, ERC), or future projected higher concentrations (10x ERC, 100x ERC). Measured microplastic concentrations were similar to their nominal values, confirming that PP particles and PET fibers were present at the desired concentrations and available for ingestion by individual damselfish. Throughout the 128-h depuration period, the 88 experimental fish were sampled 2, 4, 8, 16, 32, 64 and 128-h post microplastic exposure and their gastrointestinal tracts (GIT) analyzed for ingested microplastics. While damselfish ingested both experimental microplastics at all concentrations, body burden and depuration rates of PET fibres were significantly larger and longer, respectively, compared to PP particles. For both microplastic types, exposure to higher concentrations led to an increase in body burden and lower depuration rates. These findings confirm ingestion of PP particles and PET fibers by P. amboinensis and demonstrate for the first time the influence of microplastic characteristics and concentrations on body burden and depuration rates. Finally, despite measures put in place to prevent contamination, extraneous microplastics were recovered from experimental fish, highlighting the challenge to completely eliminate contamination in microplastic exposure studies. These results are critical to inform and continuously improve protocols for future microplastics research, and to elucidate patterns of microplastic contamination and associated risks in marine organisms.